Key ideas in human thought - McLeish, Kenneth 1940- (Facts on File, 1993)
Spanning all disciplines throughout the ages, Key Ideas in Human Thought is the consummate guide to intellectual history. Assembled for the nonspecialist by a board of academic experts, this rich compendium provides 2,500 explanatory essays on the most important concepts that have shaped the modern world. Arranged alphabetically, terms encompass all fields of inquiry, from science to history, economics to literature, mathematics to music. This is where to find a lode of information on an extraordinary range of terms familiar and unfamiliar, complex and (apparently) simple, broad and narrow, such as post-modernism, atonality, chaos theory, structuralism, civilization, beauty, virtue. To give a full understanding of each term, essays go beyond mere definitions to explore why certain concepts have become so important. Each entry sets the term in historical context, noting the contributions of major artists, scientists, thinkers and researchers as well as the influences of competing theories. An examination of how the concept fits into current thinking and where it may lead us in the future completes the store of information for each idea. Suggested reading lists and extensive cross-referencing are included throughout to make this the first and foremost source of its kind. A brilliant combination of sophistication and accessibility, Key Ideas in Human Thought mines the breadth and depth of intellectual history as no other book does. With its wealth of information and highly readable essays, this lavish resource is an invaluable addition to every personal library.